Strategic Growth via Mergers & Acquisitions : An Empirical Study of Post-Acquisition Performance - Wangdi, Sherab; Paul, Raju; Roy, Dipen (Indian Journal of Finance, 2024)
Purpose : The study aimed to evaluate the effects of mergers and acquisitions (M&As) on acquiring firms’ performance, addressing conflicting claims by various researchers. It began with a review of merger theories and proposed alternative research methods to better reflect the true impact of M&As on firm performance. Methodology : The study analyzed changes in post-acquisition stock prices, net profits, and sales of acquiring firms using cross-sectional data from 27 randomly selected acquisitions completed between 2007 and 2020. Both parametric and non-parametric tests were conducted to draw reliable conclusions. Findings : The results indicated that instead of relying on short-term data, scholars should use data from a broader period to assess the impact of M&As. Long-term studies confirmed that M&A strategies were effective in achieving growth and market power. The findings resolved previous conflicts in the literature, showing that longer-term data aligned with merger theories, whereas short-term data often produced misleading results. Implications : The study provided insights into the true effects of M&As on business survival and growth. It suggested that investors seeking long-term benefits should invest in purchasing businesses and holding their shares for a considerable amount of time, and it provided advice for future studies. Originality : Most prior studies relied on short-term data (1 year post-M&A). This study employed both short-term and longer-term data (3 years post-M&A) using multiple performance metrics, offering a novel research design that was the first of its kind in this field.